Pemberian Cairan Parental Pada Anak - Harun Alrayid Harun Alrasyid (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1981)
The aim of parenteral fluid therapy in the child is to maintain body fluid and electrolyte balance and nutrition. Fluid and electrolyte balance in the child is more labile than in the adult.In the Department of Child Health, parenteral fluid therapy is used in:I. Gastroenteritis with severe dehydration.2. Dengue hemorrhagic fever and dengue shock syndrome.3. Premature infants, peritonitis, protein calorie malnutrition etc. for parenteral nutrition.The fluids frequently used are:1. Ringer lactate and 5% dextrose in half saline or a quarter saline according to age in gastroenteritis with severe dehydration.2. Ringer lactate and/or plasma, sometimes plasma expander, in dengue hemorrhagic fever and dengue shock syndrome.3. Aminofusin for parenteral nutrition.The dose and the composition of fluid administered are based on the severity of dehydration or shock, the aim of therapy and the composition of fluid loss.Key Words: parenteral fluid - rehydration -- shock - nutrition - low birth weight infant